Miniaturized Printed Inverted-F Antenna for Internet of Things: A Design on PCB with a Meandering Line and Shorting Strip - Cheuk Yin Cheung; Joseph S. M. Yuen; Steve W. Y. Mung (International Journal of Antennas and Propagation)
This paper focuses on a printed inverted-F antenna (PIFA) with meandering line and meandering shorting strip under 2.4 GHz industrial, scientific, and medical (ISM) band for Internet of things (IoT) applications. Bluetooth Low Energy (BLE) technology is one of potential platforms and technologies for IoT applications under ISM band. Printed circuit board (PCB) antenna commonly used in commercial and medical applications because of its small size, low profile, and low cost compared to low temperature cofired ceramic (LTCC) technology. The proposed structure of PIFA is implemented on PCB to gain all these advantages. Replacing conventional PCB line in PIFA by the meandering line and meandering shorting strip improves the efficiency of the PIFA as well as the bandwidth. As a case study, design and measurement results of the proposed PIFA are presented.